THE TASKS OF VIETNAM WOMEN’S UNION AT THE GRASSROOTS LEVEL - Chi, Dinh Van (American International Journal of Social Science Research, 2022)
Vietnam Women’s Union (VWU) was an organization founded in 1930. Its history is closely attached to our country’s history for national independence and development. The objective of this study is to find out about the tasks of Vietnam Women's Union at the grassroots level in the new situation, based on the hypothesis: the Vietnam Women's Union at the grassroots level carrying out women's work must be compatible with each object and region, promoting the spirit of mastery, potential, creativity and the highest contribution ability of women from all walks of life, contributing to the great strength of national unity to develop the country development. With this objective, the study focuses on clarifying the following issues: 1/ the propaganda, education, and mobilization of women; 2/ the Union participate in the formulation, social criticism, and supervision of the implementation of laws, policies, and policies on gender equality; 3/ The Union mobilizes and organizes women to participate in economic development, sustainable poverty reduction, and environmental protection; 4/ Mobilizing and supporting women to build happy and sustainable families; 5/ Building and developing a good association organization; 6/ Participating in building the Party, government, Front and mass organizations. The author has used scientific research methods such as analysis and synthesis, deductive and inductive, abstraction and generalization, history, and comparison to come to general conclusions of the study.JEL Classification Codes: H8